Curcumin Oral Gel and its Relation to Salivary Tumor Necrosis Factor-Alpha and Interleukin-6 that Treated Oral Mucositis in Head and Neck Cancer Patients Undergoing Concurrent Chemoradiation - Rouaa S. Farhan; Fawaz D. Al-Aswad (Diyala Journal of Medicine, 2025)
Background: Curcumin oral gel is one example of a traditional herbal medication, it has shown potential in several pharmaceutical uses. Oral mucositis is commonly prevent and treat using magic solution, a mouthwash that contains a combination of pharmaceuticals. Tumor necrosis factor- α and Interleukin-6 are salivary cytokines stimulates the immune response and promotes inflammation during infection or other tissue damage causes inflammation. Objective: To determine the effect of curcumin oral gel on salivary tumor necrosis factor-α and interleukin-6 levels in head and neck cancer patients under concurrent chemoradiation induced oral mucositis. Patients and Methods: Two groups of forty-five patients each, with a total of ninety head and neck cancer patients receiving concurrent chemoradiation. Enzyme-linked immunosorbent assay measured salivary tumor necrosis factor-alpha and interleukin-6 levels. Oral mucositis was assessed by WHO scale. Results: Patients who took oral curcumin gel had less severe oral mucositis and lower salivary levels of tumor necrosis factor-alpha and interleukin-6. WHO scale between the two groups showed significant differences at 2 weeks (P = 0.041) and 6 weeks (P=0.02). Conclusion: Study concludes that curcumin oral gel might reduced salivary tumor necrosis factor-alpha and interleukin-6 levels and may serve as an alternative treatment for oral mucositis resulting from chemoradiation. Keywords: Head and neck cancer, Concurrent chemoradiotherapy, Oral mucositis, Curcumin, Tumor necrosis factor-alpha, Interleukin-6.